The Distribution of Income Among Income Taxpayers in the United States, 1863-1935 - Tucker, Rufus S. (Quarterly Journal of Economics, 1938)
Method of analysis, 548.— Taxable Income, 550.— Spending Power, 552.— Earning Power, 555.— Comparison with total national income, 559.— The Income Tax of 1894, 560.— Civil War Incomes, 561.— Distribution of Taxpayers by Income Classes, 562.— Distribution of Income by Income Classes, 565.— Comparison of Average and Modal Incomes, 567.— Distribution of Incomes of Constant Purchasing Power, 570.— Comparison with British figures, 577.— Shifting Composition of Wealthy Group, 583.— Conclusions and Comments, 585.